Analysis of alkaline phosphatase, soluble acid phosphatase, low density lipoprotein and vitamin D binding protein gene polymorphisms as possible gene-candidates participating in mineral bone density determination in women with primary osteoporosis in postmenopause - M Y Krylov; V A Myakotkin; L L Benevolenskaya (Научно-практическая ревматология)
Objective. To investigate the distribution of alkaline phosphatase (ALPL), acid phosphatase I (ACPI), receptor lipoprotein low density (LDLR) and vitamin D binding protein (GC) genotypes in osteoporotic ana nonosteoporotic postmenopausal women and the possible associations these genotypes with bone mineral density (BMD). Material and methods. In this study ALPL, ACPI, LDLR and GC genotypes were determined by polymerase chain reaction (PCR) or PCR-RFLP analysis. Results. We observed significant the associations between BMD of the femoral neck and SS and 2F GC genotypes (0.696 ± 0.010 and 0.654 ± 0.020 gr/cm 2, p < 0.05) but not with lumbar spine in the osteoporotic women. The associations weren't observed between ALPL, ACPI. LDLR genotypes and BMD. Conclusion. These new data showed important role of the GC gene in determination of bone mineral density of the femora! neck in postmenopausal women with osteoporosis.